Attitude Towards Pre-Marital Counselling Among Undergraduate Studentsof Ambrose Alli University, Ekpoma, Edo State - Gloria Omolego Omi-Ujuanbi; Obaze Agbonluae Osumah (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
This study investigated the attitudes of undergraduates at Ambrose Alli University, Ekpoma, towards premarital counseling and examined whether gender and religiosity influenced their attitudes towards premarital counseling. The research was motivated by the need to understand the perceptions of young adults regarding counseling services as a preventive measure for marital challenges. The study adopted a descriptive survey method, involving 273 undergraduates as the sample population. Data were collected using a self-developed questionnaire. The mean (X) and standard deviation (S.D) were utilized for descriptive analysis, while t-test statistics for two independent samples were employed to test the research hypotheses at a 0.05 significance level. The findings revealed that undergraduates in Ambrose Alli University exhibit a negative (restrictive) attitude towards premarital counseling. Additionally, gender and religiosity were found to have no significant influence on these attitudes. The study concludes that the negative perception of premarital counseling among students may hinder their ability to benefit from its preventive and informative potential. It is recommended that guidance counselors be employed in all tertiary institutions to provide students with orientation and information services regarding premarital counseling. These findings imply the need for institutional interventions to address misconceptions and promote the relevance of counseling services.